Peripheral vascular catheter use in Latin America (the vascular study): A multinational cross-sectional study - Walker, Rachel M.; Pires, Maria Paula Oliveira; Ray-Barruel, Gillian; Cooke, Marie; Mihala, Gabor; Azevedo, Silvia Schoenau; Peterlini, Maria Angelica Sorgini; Felipe, Marcelle Di Angelis Ambar; Álvarez, Cirlia Petrona; Quintanilla, Marcela; Corzo, Martha Claudia; Villareal, Gabriela Cortez; et al. (Frontiers in Medicine, 2023)
Background: Peripheral intravenous catheter (PIVC) insertion is one of the most common clinical procedures worldwide, yet little data are available from Latin America. Our aim was to describe processes and practices regarding PIVC use in hospitalized patients related to hospital guidelines, characteristics of PIVC inserters, prevalence of PIVC complications, and idle PIVCs. Methods: In 2019 we conducted a multinational, cross-sectional study of adult and pediatric patients with a PIVC in hospitals from five Latin American countries: Argentina, Brazil, Chile, Colombia, and Mexico. We used two data collection tools to collect hospital guidelines and patient-specific data on the day of the study. The Vessel Health and Preservation model guided synthesis of the study aims/questions and suggested opportunities for improvement. Results: A total of 9,620 PIVCs in adult (86%) and pediatric inpatients in 132 hospitals were assessed. Routine replacement 8–72 hourly was recommended for adults in 22% of hospitals, rather than evidence-based clinical assessment-based durations, and 69% of hospitals allowed the use of non-sterile tape rather than the international standard of a sterile dressing. The majority (52%) of PIVCs were inserted by registered nurses, followed by nursing assistants/technicians (41%). Eight percent of PIVCs had pain, hyperemia, or edema, 6% had blood in the extension tubing/connector, and 3% had dried blood around the device. Most PIVCs had been inserted for intravenous medications (81%) or fluids (59%) in the previous 24 hours, but 9% were redundant. Conclusions: Given the variation in policies, processes and practices across countries and participating hospitals, clinical guidelines should be available in languages other than English to support clinician skills and knowledge to improve PIVC safety and quality. Existing and successful vascular access societies should be encouraged to expand their reach and encourage other countries to join in multinational communities of practice.